The difference of physical activity and gender: a secondary data analysis of non-communicable disease among farmers in public health center of Jember Regency, Indonesia - Ningsih, Ayu Putrias; Susanto, Tantut; Aini, Latifa; Khoidi, Mokhlas (Universitas Sari Mulia, 2022)
Background: Lack of physical activity can increase the risk of Non-Communicable Diseases (NCDs) among farmers regarding their activities while working.Objectice: This study was to analyze differences physical activity among farmers regarding their gender in Integrated of NCDs Post of Pakusari Health Center, Jember.Method: A survey with a retrospective cohort study design based on secondary data analysis of Integrated of NCDs Post from January to October 2020 was performed among 112 farmers. The characteristics of participants and physical activity were measured through Healthy Registered Card of Integrated of NCDs Post. Chi square test was used to answer the research objectives (p value 0.05).Results: The results showed that there were differenced physical activity between male and female farmers (χ2=9.172; p-value=0.002). Physical activity of male farmers is dominated by sufficient physical activity (79.2%) and female farmers are dominated by lack of physical activity (55.7%). Male farmers were 1.79 times more likely to have sufficient physical activity than female farmers (RR= 1.79; 95% CI=1.31-2.45; p-value= 0.002.).Conclusions: The physical activity among farmers are differenced by gender. Therefore, fulfillment of physical activity by gender should be improved among farmers to reduce NCDs.Key Words: Physical Activity, Farmer, Gender, Non-Communicable Disease, Posbindu PTM